Предмет:
МатематикаАвтор:
анонимВычислим значения выражений:
1) (1,2 * 10^5) * (5 * 10^(-3)) = 1,2 * 5 * 10^5 * 10^(-3) = 1.2 * 5 * 10^(5 - 3) = 1.2 * 5 * 10^2 = 1.2 * 5 * 100 = 12 * 50 = 600;
2) (4 * 10^12) * (1,5 * 10^-7) = 4 * 1.5 * 10^(12 - 7) = 4 * 3/2 * 10^5 = 2 * 3 * 10000 = 6 * 10000 = 60000;
3) (3,6 * 10^2) : (9 * 10^-3) = 3.6/9 * 10^(2 + 3) = 0.4 * 10^5 = 4 * 10^4 = 40000;
4) (5 * 10^-4) : (2,5 * 10^9) = 5/2.5 * 10^(-4 - 9) = 5 * 2/5 * 10^(-13) = 2 * 10^(-13).
Автор:
leahhsxvДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть